Enjoyfull Learning dan Explicit Intruction Sebagai Alternatif Model Pembelajaran dalam Meningkatkan Hasil Belajar Siswa - Zamzami Zamzami; Zulkarnaini Zulkarnaini (Jurnal Dedikasi Pendidikan, 2019)
Learning model is a systematic method or presentation technique used by educators in organizing the learning process both individually and in groups to achieve learning goals. The purpose of this study is to compare the percentage of the students learning outcomes through Enjoyfull Learning with Explicit Instruction. The research subjects were 50 high school students. This research uses quasi-experimental methods with a quantitative approach. Data collection was collected through giving tests and analyzed by SPSS. The results showed that the students' ability to understand learning after the application of the Enjoyfull Learning model was 81.64 in the pre-test and 82.58 in the posttest, for the students learning outcomes, the pre-test was 85.18 and 86.44 in the post-test. While the results of the students' ability to understand learning by applying Explicit Intruction learning model was 79.54 in the pre-test and 80.22 in the post-test, for student learning outcomes, the pre-test wais 81.44 and 82.44 in the post-test . Thus it can be assumed that the Enjoyfull Learning model is preferred by students so that it is more appropriate to be applied to improve the students learning outcomes, but still pay attention to certain adjustments in order to obtain maximum learning outcomes.